Insecure Behavior of Students using Social Media and its Implications in Counseling Services - Rahmi, Aulia; Irman, Irman; Ardimen, Ardimen; Hardi, Emeliya; Carol, Tuomi (Yayasan Minang Darussalam, 2024)
This research is motivated by the insecure behavior of students who use social media. Researchers see that there are various problems that arise because social media users focus primarily on student insecure behavior. The purpose of this research is to find out the forms of insecure behavior of students who use social media, to find out the causes of insecure behavior of students who use social media, to find out the effects of the insecure behavior of students who use social media, to find out the implications of counseling services on the insecure behavior of students who use social media. The method used is a qualitative method with a descriptive approach. Data collection techniques are by observation, interviews and documentation. The primary data source in this study is the student occupants of the limo boarding house. The technique of data analysis and data interpretation is to collect data from interviews and observations, make conclusions and verify the data. The technique used to guarantee data validity is data triangulation, namely source triangulation, technical triangulation, and time triangulation. The results of the study found that the insecure behavior of students who use social media and its implications for counseling services at the Limo Kaum boarding house can change students' mindsets and insecure behavior, related to the use of social media to become healthier, positive, and adaptive.